Social representation of palliative care in the Spanish printed media: A qualitative analysis. - José Miguel Carrasco; Beatriz Gómez-Baceiredo; Alejandro Navas; Marian Krawczyk; Miriam García; Carlos Centeno (PLoS ONE, 2019)
BACKGROUND:Lack of social awareness is a major barrier to the development of palliative care. Mass media influences public opinion, and frequently deal with palliative care contributing to its image and public understanding. AIM:To analyse how palliative care is portrayed in Spanish newspapers, as well as the contribution made by the press to its social representation. DESIGN:Based on criteria of scope and editorial plurality, four print newspapers were selected. Using the newspaper archive MyNews (www.mynews.es), articles published between 2009 and 2014 containing the words "palliative care" or "palliative medicine" were identified. Sociological discourse analysis was performed on the identified texts on two levels: a) contextual analysis, focusing on the message as a statement; b) interpretative analysis, considering the discourse as a social product. RESULTS:We examined 262 articles. Politician and healthcare professionals were the main representatives transmitting messages on palliative care. The discourses identified were characterised by: strong ideological and moral content focusing on social debate, strong ties linking palliative care and death and, to a lesser degree, as a healthcare service. The messages transmitted by representatives with direct experience in palliative care (professionals, patients and families) contributed the most to building a positive image of this healthcare practice. Overall, media reflect different interests in framing public understanding about palliative care. CONCLUSION:The knowledge generated about how palliative care is reflected in the printed media may help to understand better one of the main barriers to its development not only in Spain, but also in other contexts.